Characteristics of local and system immunity, and features of cancer stem cells in patients with different stage, dynamics and prognosis of colorectal carcinoma - E. Yu. Zlatnik; I. A. Novikova; E. S. Bondarenko; E. P. Uljanova; A. O. Sitkovskaya (Медицинская иммунология, 2022)
Clinical prognosis in malignant tumors` is among the most challenging problems of contemporary medicine. It is thought to depend on both biologic properties of tumor cells and patients` immune status. The features of tumor cells and immune reactions are closely interrelated and mutually conditioned. Therefore, possible application of their characteristics as prognostic markers is of great fundamental and clinical importance. The aim of our study is to find out the most significant immune factors for prognosis of colorectal cancer (CRC) based on estimation of local and system immune factors, and some characteristics of tumor cells in the patients at various stages of the disease and different clinical course. Cellular factors of immunity and cytokines were studied in blood and tumor tissue of 299 patients with colorectal cancer (stages I-IV). Malignant cells expressing stem cell markers CSC), MHC and PDL-1 molecules were also counted in the tumor tissue. Blood samples were drawn prior to operation, and tissue samples were taken during surgery being the 1st line of treatment. Flow cytometry techniques (FCM), immunohistochemistry (IHC), and ELISA approach were employed. We have compared data on the patients at different CRC stages (with or without local and distant metastases), as well as cases with different course of the disease (evolving distant metastases and fatal outcome during period of observation). Our results demonstrated increased amounts of NK-cells and IL-6 concentration, along with decreased percentage of blood CD4+ cells in the patients with local metastases, as well as higher CSC numbers in malignant tissue. The initially generalized CRC cases with distant metastases were characterized by high levels of blood IL-6, monocytes and granulocytes responding to fMLF, while in tumor tissue elevated amounts of NKT, CSC and decreased expression of MHC and PDL-1 were observed on tumor cells, like as lower PD-1/ PDL-1 expression on tumor-infiltrating lymhocytes. Unfavorable CRC dynamics, i.e., metastasizing during the observation period was preceded by increased levels of IL-10 in blood, NK cells with poor cytotoxicity, monocytes and granulocytes responding to fMLF. In tumor tissue, overexpression of CSC markers and hypo-expression of MHC on tumor cells were noted. Fatal outcome was preceded by elevation of blood IL-6levels, tissue levels of NKТ and CSC percentages, along with decreased NK cells subset (CD16dimCD56bright) in blood, and decline of MHC-expressing cells in the tumor. Thus, high blood levels of IL-6 and IL-10, fMLF-responding monocytes and granulocytes, as well as elevated amounts of NKT and CSC, hypo-expression of MHC in tumor tissue could be considered prognostic markers of unfavorable course in CRC patients. Decrease of PD-1/PDL-1 expression on tumor cells and lymphocytes from its microenvironment in advanced CRC is of special attention, because checkpoint inhibitors are prescribed in such cases.